PENGARUH RETURN ON ASSETS (ROA), DEBT TO TOTAL ASSET RATIO (DAR), INTENSITAS ASET TETAP, SIZE DAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP PENGHINDARAN PAJAK - Kristanti Rahman; Awit Setyawati (JURNAL EKONOMI, 2020)
This study aims to determine and analyze the effect of Return on Assets (ROA), Debt to Total Asset Ratio (DAR), Fixed Asset Intensity, Size and Corporate Social Responsibility (CSR) on Tax Avoidance. The population in this study were Metal Manufacturing Companies and the like which were listed on the Indonesia Stock Exchange (BEI) 2014-2018. The research sample was determined using purposive sampling method. The type of data used is secondary data and the total sample selected in this study were 5 companies. The data analysis method used is multiple linear regression analysis. The results of the analysis show that simultaneously, Return on Assets (ROA), Debt to Total Asset Ratio (DAR), Fixed Asset Intensity, Size and Corporate Social Responsibility (CSR) affect tax avoidance. This means that the higher the Return on Assets (ROA), Debt to Total Asset Ratio (DAR), Fixed Asset Intensity, Size and Corporate Social Responsibility (CSR) will lead to increased tax avoidance. Debt to Total Asset Ratio (DAR) and Fixed Asset Intensity partially have no effect on tax avoidance. This means that the higher the Debt to Total Asset Ratio (DAR) and the Intensity of Fixed Assets will not have an effect on increasing tax avoidance. Keywords : Tax Avoidance, Return on Assets (ROA), Debt to Total Asset Ratio (DAR), Fixed Asset Intensity, Size and Corporate Social Responsibility (CSR)